PENILAIAN KINERJA KEUANGAN PT. SARANA MEDITAMA METROPOLITAN TBK SEBELUM DAN SELAMA PANDEMI COVID-19 (2018-2021) DENGAN MENGGUNAKAN ANALISIS TREND - Rossalia Irine Larasati (Bajang Institute, 2023)
After the year ends, one of the important tasks of management or investors is to analyze the company's financial statements. Through this analysis, the development of a company can be known. However, in the last 3 years, Indonesia experienced an economic recession due to the Covid-19 pandemic.This study uses a descriptive quantitative approach, with PT. Sarana Meditama Metropolitan Tbk, a service company in the health sector or hospital, as a research subject on the Indonesia Stock Exchange in the 2018-2021 period. To find out whether the Covid-19 pandemic affects the company, financial performance can be calculated using trend analysis and profitability ratios. The results showed that the financial condition of PT. Sarana Meditama Metropolitan fluctuates from year to year. However, this condition is still considered reasonable because the company's profitability ratios, such as NPM, ROA, and ROE ratios, have values above the industry average. Overall, the results of trend analysis and profitability ratios were found in line where trend analysis showed a good state of financial condition seen from the balance sheet and profit and loss, this statement was also supported by the results of the profitability ratio where the results of NPM, ROA, and ROE got values above the industry average where these results showed financial performance at PT. Sarana Meditama Metropolitan Tbk is good.